(untitled) (Journal of the College of Basic Education, 2026)
This research focused on the urban aspect of the monasteries of Mosul in the book Al-Khazal and Al-Dal by Yaqut Al-Hamawi (262 AH / 1229 AD). The urban aspect represents a reflection of the civilizational, religious and cultural aspects of peoples throughout the ages. The monasteries in this research do not only show the urban aspect, but also clarify their religious importance and the rituals and ceremonies that follow them, which may differ from one monastery to another and from one region to another. Mosul was known for its many monasteries that were not limited to places of worship only, but were rest stops for travelers and guest houses. Many monasteries were of special importance due to the presence of sulfur springs in them, and some of them were centers for healing many diseases. Some monasteries were characterized by an educational and religious character together, as they contained a school that may specialize within a religion or A specific religious group, which contributed to the interest and development of these monasteries in Mosul is the distinguished location of the city of Mosul and the location of the monasteries, as Mosul is distinguished by the softness of its air and the sweetness of its water, which made the monasteries in it distinct and excellent from all other cities. These features in the monasteries are an excellent place to hold the celebration of religious holidays related to Christ for the elite and the common people among them